Badut Jalanan: Badut yang Tak Lagi Dianggap Menghibur (International Forum of Researchers and Lecturers, 2023)
The occurrence of the '19 covid pandemic requires people to reduce activities, and even stop outdoor activities as an effort from policies carried out by the government to stop the spread of '19 covid. But of course, this policy makes people confused, especially people who have jobs that require them to leave the house and do outdoor activities. Not only that, the country's unstable economic condition also makes many companies in Indonesia decide to terminate their cooperation with employees unilaterally to maintain the financial stability of their companies. Therefore, during the pandemic, so much new unemployment was caused by layoffs. But because of this, many people have lost their jobs and those who lack the ability and skills in a field of work are forced to enter a job, or maybe it cannot also be called a job, namely begging, and one form of beggar today is street clowns. This research will focus on the figure of street clowns at the Mastrip Roundabout Red Light, as well as the background that makes them eventually become street clowns. This research is a research that uses qualitative methods with a phenomenological approach, and the theoretical basis used is the theory of Social Action proposed by Max Weber. Data collection using observation, interviews, and documentation.